The relationship between consumption of animal products and expenditure levels with Quality of Life Scores (SF-36) by veterinary students in Turkey - Tekindal, M. A.; Cevriml, M. B.; Akin, A. C.; Mat, B.; Arikan, M. S.; Polat, M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The present study aimed to calculate the quality of life scores (Short Form-36) of veterinary students in Turkey and review their scores with regards to different socio-demographic characteristics. A total of 1211 students studying veterinary medicine in 26 different faculties in Turkey were selected by stratified sampling method and were asked questions concerning their consumption of and expenditures on foods of animal origin using the SF-36 questionnaire between October and December 2018. Significant differences were found between SF-36 components in terms of year level, gender, accommodation status, income level, and level of expenditures on foods and foods of animal origin (P<0.01). With the increase in the size of the budget set aside for animal products, the scores in the domains of physical functioning, vitality, mental health, pain, and general health perception also enhanced, and statistically significant differences were found (P<0.01). The low quality of life scores of the veterinary students can be improved by increasing their income level and consumption of foods of animal origin. This will ensure that they are energetic and have the desired level of mental and general health perceptions.
Keywords: expenditure; foods of animal origin; income; quality of life; student; veterinary medicine